(3GdbQV GdeUQaj cUhQI ef UhQ GdGFJeGf h COGI ddJehjd (B:s (3OQGSI ebGQfI Hjf GdJYGed GdeUQaj h Gdabg GdGSdGej (B/s - (3MSf GdSHc, UHQj eUWais ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2011)
(3eGgjI YbO GdbQV GdeUQaj h CfhGYg h GdWHjYI GdbGfhfjI dg , VeGfGJ GdbQV GdeUQaj h BKGQg h GfbVGhg , GdeYGedI GdVQjHjI ddbQV h ahGFOg , ehba Gdabg GdGSdGej ef GdahGFO Ydi GdbQV GdeUQaj h GdHOjd GdTQYj dgGs
Keywords: (3GdJehjds; (3GdbQhV GdHfcjIs; (3bQhV GdGFJeGfs